The Role of Family in Improving of PHBS Behavior to Adapt a New Habits (AKB) to Prevent from High Risk of Covid-19 in Elderly - Rahmania Ambarika; Angga Ladzi Syafroni; Novita Ana Anggraini (Journal of Global Research in Public Health, 2022)
Elder people are an age group that have experienced a decreasing body function system in many aspects, such as physical, psychological and social. The existence of these limitations will greatly affect the ability/independence in carrying out Clean and Healthy Behavior (PHBS) in efforts to prevent from Covid-19. The elderly are also included in the category with a high risk of being susceptible to Covid-19 because most of the elderly people have comorbidities such hypertension and diabetes mellitus, etc. One of the factors related to PHBS in the elderly people is family support. The purpose of this study was to determine the influence of the role of the family on PHBS behavior in adapting to new habits (AKB) to prevent high risk of Covid-19 in the elderly. This research design used an observational with a cross sectional approach. The population was all elderly people with a total of 40 elderly. The samples were 36 respondents using Simple Random Sampling technique. The independent variable was the Family Role and the dependent variable was PHBS behavior adaptation to new habits. The data collection using questionnaires and the data analysis used Spearman Rank at α = 0.05.The results showed that most of the respondents had a family role in the support  category as many as 23 respondents (63%) and most of the respondents 23 (63%) had PHBS behavior adapted to new habits in the moderate category. The results of the Spearman Rank obtained a p-value (0.000) < α (0.05) with a correlation coefficient of 0.698 which means a strong correlation. Thus, H0 is rejected and H1 is accepted which means there is an influence between the family role and PHBS behavior to adapt to new habits (AKB) to prevent  high risk Covid-19 in elderly.The role of the family in caring for the elderly people is the main support system for them. In maintaining their health, the family can do things such as physical, psychological, social and spiritual care, so there will be positive behavioral changes.